Determining the effect of non-condensable gas on a two-phase ammonia heat transfer loop of the satellite - Buchko, Oleksii; Gorbenko, Gennady; Rohovyi, Yevhen; Reshytov, Edem; Turna, Rustem (Eastern-European Journal of Enterprise Technologies, 2024)
It is advisable to design thermal management systems for high-power stationary satellites and specific ground applications using two-phase mechanically pumped loops with ammonia as the coolant. During prolonged operation in orbit, the accumulation of non-condensable gases can occur due to radiolysis and chemical reactions. The issues related to the effect of non-condensing gas on system parameters and performance have not yet received sufficient attention. The study of the distribution of non-condensable gas in the loop was performed by calculation-theoretical and experimental methods in a heat transfer loop with a Heat-Controlled Accumulator. Part of the gas accumulates in the steamgas zone of the Heat-Controlled Accumulator and affects the pressure value at a set temperature. The other gas is dissolved in liquid ammonia. This impacts the overheating of the cooled device when the heat load is switched on, the heat transfer intensity during boiling, and the cavitation reserve at the pump inlet. Accumulation of non-condensable gas up to 0.075 mol nitrogen/kg ammonia, concentration of dissolved gas in the liquid up to 5.3⋅10–4 mol/mol of the mixture does not significantly impact the parameters and performance of the system. But, if the aim is to precisely ensure the boiling temperature of the coolant or the cavitation reserve, the amount of necessary correction of the control parameters is up to 2.5 K. The results of the investigation can be used in the design of two-phase heat transfer loops for satellites and other applications, in particular, for the selection of the design and location of gas traps